Assessing the resurgent irrigation development program of the Philippines: Institutional arrangements for irrigation governance - Agnes C. Rola; Therese R. Olviga; Francis John F. Faderogao; Chrislyn Joanna P. Faulmino (Philippine Institute for Development Studies (PIDS), 2020)
This project aims to evaluate the effectiveness and efficiency of the government's irrigation program. It focuses on technical, physical, and institutional aspects of performance of both national (NIS) and communal irrigation systems (CIS), and selected case studies. The governance component describes and analyzes the governance mechanisms of the entire irrigation project cycle from planning to monitoring and evaluation. It draws on the findings from the other studies within this project, while focusing on governance, particularly higherlevel issues cutting across national and communal systems and also across the other water sector agencies. The project was done in two cycles. Cycle 1 conducted in 2015 covered the seven regions of Luzon. Respondents were National Irrigation Administration (NIA) officers from the 7 Regional Irrigation Offices (RIO) and 14 Irrigation Management Offices (IMO), in the following provinces: 1) Laguna; 2) Ilocos Norte; 3) Cagayan; 4) Isabela; 5) Nueva Vizcaya; 6) Benguet; 7) Pangasinan; 8) Nueva Ecija; 9) Pampanga; 10) Camarines Sur; and 11) Occidental Mindoro. The Cycle 2 covers NIS and CIS in eight (8) IMOs and 6 RIOs in the Visayas and Mindanao regions. The 8 selected Irrigation Management Offices (IMOs) visited for this study are in the following provinces: 1) Leyte; 2) Bohol; 3) Iloilo; 4) Capiz 5) North Cotabato; 6) South Cotabato; 7) Davao del Sur;; and 8) Bukidnon. Correspondingly, the 6 Regional Irrigation Offices (RIOs) are Regions 6,7,8,10,11and 12, where only four were visited. The CIS and NIS IA level governance data were gathered by the technical teams. Whenever possible, data from Cycle 1 gathered from Luzon were integrated in this report. [...]
Keywords: 330; Institutional arrangements; irrigation governance; water governance; free irrigation policy; water rights; project cycle